Fungsi Adaptasi Sosio-Kultural Komunitas Muna Perantauan dalam Masyarakat Multikultural di Kota Bitung Provinsi Sulawesi Utara - Musafar; Hadirman (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2020)
The purpose of the article is to describe the socio-cultural adaptation function of the Muna community to the multicultural community ini Bitung City. The method used ini this research is descriptive qualitative. The result showed that ini order to suvive in the City of Bitung, the Muna community does social-cultural adaptation. The social-cultural adaptations has a function for the Muna community overseas, namely (1) the function of strengthening identity; (2) economic function; and (3) social solidarity function.